Reciprocal Regulation of Th1- and Th2-Cytokine-Producing T Cells during Clearance of Parasitemia in Plasmodium falciparum Malaria - Winkler, Stefan (American Society for Microbiology, 1998)
Flow cytometry for the intracellular detection of T-cell cytokines was performed for 15 Gabonese patients during acute uncomplicated Plasmodium falciparum malaria. A striking expansion of CD4(+) and CD8(+) T cells producing gamma interferon (IFN-γ) was found during drug-induced clearance of parasitemia, paralleled by a decrease of interleukin-2 (IL-2) production. The frequency of IL-4- and IL-13-producing CD4(+) cells gradually decreased, whereas the frequency of T cells producing IL-2(+)–IFN-γ(+), IL-4(−)–IL-5(+), and IL-4(+)–IL-5(+) cytokines as well as IL-4(+)–IFN-γ(+) and IL-13(+)–IFN-γ(+) cytokines was not significantly altered. The capacity for IL-10 production within the CD4(+) subset increased due to an expansion of both IL-10(+)–IFN-γ(−) and IL-10(+)–IFN-γ(+) cytokine-expressing cells. Thus, a more pronounced Th2-driven immune response during acute untreated P. falciparum infection with a shift towards Th1 responsiveness induced by parasite clearance is suggested.